Assessing the influence of injection temperature on CO2 storage efficiency and capacity in the sloping formation with fault. (15th January 2021) - Jing, Jing; Yang, Yanlin; Tang, Zhonghua
Abstract: Complex factors can affect carbon dioxide (CO2 ) geological storage efficiency and capacity. In this paper, a three-dimensional (3D) conceptual model of the Shiqianfeng formation in the Ordos basin was established (a total of 16 sets of schemes) to study the influence of injection temperature on CO2 storage efficiency and migration safety in the sloping formation with a fault. In addition, storage capacity is investigated for CO2 storage site selection. The results show that injection temperature and formation slope have a significant effect on CO2 storage efficiency. Faulting provides a possible channel for CO2 leakage. High injection temperature is more likely to cause CO2 leakage in the sloping formation. When the injection temperatures are 11, 31.5, 51 and 71 °C in the 15° slope formation, the time points of CO2 leakage are 200, 170, 150 and 140 years, respectively. The lower injection temperature results in a higher CO2 concentration near the injection well and a closer migration distance of dissolved CO2 . The larger the formation slope is, the farther the dissolved CO2 migration distance will be. The higher injection temperature results in a greater gas phase, dissolved phase, and total CO2 storage amount in the whole formation. The larger the formation slope is, the smaller the CO2 storage capacity will be for CO2 injected over 20 years. However, the larger formation slope resulted in a smaller gas phase and larger storage amount of the dissolved phase CO2 for CO2 migration after 140 years. The influence of the formation slope on the dissolved CO2 migration safety is more obvious than that of injection temperature. However, the influence of the injection temperature on CO2 storage capacity is more obvious than that of the formation slope. Highlights: 3D models with injection temperatures and formation slopes were built. Plume migration and volumetric storage were discussed. CO2 leakage occurred in different injection temperature formations. The results will help to inform site selection for future CCS projects.